Understanding consumers’ non-compensatory and heterogeneous preferences for electric vehicles - Huo, Jinghai; Kim, Eui Jin; Bansal, Prateek (Energy Policy, 2024)
Previous studies eliciting preferences for battery electric vehicles (BEVs) assume the compensatory behavior of consumers, where all attributes of available alternatives are weighted in reaching a choice. However, consumers might follow non-compensatory rules where BEVs may become unattractive beyond certain attribute thresholds (i.e., cutoffs). To investigate non-compensatory and heterogeneous BEV preferences, we estimate a latent class model with attribute cutoffs using the preferences of over 800 potential car buyers from Singapore. We distinguish between early and late BEV adopters and their behaviors, highlighting the relevance of our findings in accelerating BEV adoption across various stages. For example, while current incentives primarily target reducing upfront costs, subsidizing electricity could be particularly effective for late adopters who prioritize future savings on operational expenses. Additionally, increasing the availability of BEV models from top-selling brands could effectively drive early BEV adoption in Singapore because early adopters place higher value on the availability of BEV models from the preferred brands when it is below their cutoff.
Keywords: 'current; Attribute cutoff; Battery-electric vehicles; Compensatory behavior; Discount rates; Latent class model; Non-compensatory; Operational expense; Singapore; Vehicle modelling; Attribute cutoffs; Discount rate; Electric vehicle; Non-compensatory